Chimeric G‐CSF Receptor‐Mediated STAT3 Activation Contributes to Efficient Induction of Cardiomyocytes from Mouse Induced Pluripotent Stem Cells. Issue 2 (17th September 2019) - Tsukamoto, Tasuku; Sogo, Takahiro; Ueyama, Tomoe; Nakao, Shu; Harada, Yukihiro; Ihara, Dai; Akagi, Yuka; Kida, Yasuyuki S.; Hasegawa, Koji; Nagamune, Teruyuki; Kawahara, Masahiro; Kawamura, Teruhisa
Abstract: Producing a sufficient number of cardiomyocytes from pluripotent stem cells has been of great demand for cardiac regeneration therapy. However, it remains challenging to efficiently differentiate cardiomyocytes with low costs. Reportedly, granulocyte colony‐stimulating factor (G‐CSF) receptor (GCSFR) signaling activates signal transducers and activators of transcription (STAT) signaling and enhances cardiac differentiation from embryonic stem cells or induced pluripotent stem cells (iPSCs). To economically and efficiently produce cardiomyocytes from iPSCs through GCSFR/STAT axis activation, we constructed antibody/receptor chimeras that can respond to an inexpensive small molecule. Single‐chain Fv of anti‐fluorescein (FL) antibody was ligated to transmembrane/cytoplasmic domains of GCSFRs, enabling transduction of GCSFR signaling in response to FL‐conjugated bovine serum albumin (BSA‐FL) as an alternative ligand. Mouse iPSC lines constitutively expressing these chimeric receptors exhibited increased BSA‐FL‐induced STAT3 phosphorylation in a dose‐dependent manner, which was abolished by an inhibitor of Janus tyrosine kinase (JAK). In addition, BSA‐FL stimulation also increased the incidence of beating embryoid bodies and upregulated cardiac‐specific gene expressions after differentiation in these iPSC lines. Therefore, the chimeric GCSFRs activated endogenous GCSFR signaling at least via the JAK/STAT3 pathway, thereby enhancing cardiac differentiation from iPSCs. This approach, as an economical strategy, could contribute to stem cell‐based cardiac regeneration therapy. Abstract : The authors constructed chimeric granulocyte colony‐stimulating factor receptors (GCSFRs) in which single chain Fv was ligated to transmembrane/cytoplasmic domains of GCSFR. The chimeric GCSFRs were activated in response to an inexpensive alternative ligand, and enhanced cardiac differentiation from induced pluripotent stem cells. This work could contribute to stem cell‐based cardiac regeneration therapy as an economical and powerful strategy.